2016
DOI: 10.1038/srep36738
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of radiation-induced point defects by rhenium and osmium interstitials in tungsten

Abstract: Modeling the evolution of radiation-induced defects is important for finding radiation-resistant materials, which would be greatly appreciated in nuclear applications. We apply the density functional theory combined with comprehensive analyses of massive experimental database to indicate a mechanism to mitigate the effect of radiation on W crystals by adding particular solute elements that change the migration property of interstitials. The resultant mechanism is applicable to any body-centered-cubic (BCC) met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…This is consistent with nano-indentation observations where the presence of rhenium in tungsten had no significant effect on the hardening behaviour [54]. Rather, it has been seen through DFT that presence of rhenium in tungsten actually enhances vacancy-interstitial recombination (suggested that the vacancy suppression occurs at isolated interstitials) and suppression of void swelling, leading to the idea that addition of rhenium to tungsten can improve its radiation-resistance [55]. This of course must be balanced with irradiation-induced clustering of rhenium that sets in at high damage doses and leads to substantial hardening as rhenium clusters act as efficient obstacles to dislocation motion [56][57][58].…”
Section: Average Of Measured Between 1-2 µM (× − )supporting
confidence: 84%
“…This is consistent with nano-indentation observations where the presence of rhenium in tungsten had no significant effect on the hardening behaviour [54]. Rather, it has been seen through DFT that presence of rhenium in tungsten actually enhances vacancy-interstitial recombination (suggested that the vacancy suppression occurs at isolated interstitials) and suppression of void swelling, leading to the idea that addition of rhenium to tungsten can improve its radiation-resistance [55]. This of course must be balanced with irradiation-induced clustering of rhenium that sets in at high damage doses and leads to substantial hardening as rhenium clusters act as efficient obstacles to dislocation motion [56][57][58].…”
Section: Average Of Measured Between 1-2 µM (× − )supporting
confidence: 84%
“…rhenium (Re) and osmium (Os) are all produced under the real irradiation conditions. These elements can significantly affect the microstructure evolution of defects and complicate the defect-GB interaction processes/mechanisms described here [46][47][48][49][50][51][52][53][54][55]. First-principles calculations by Zhou et al [46] suggest that it is energetically and kinetically favorable for the W GB of Σ5(3 1 0)/[0 0 1] to trap H coming from the bulk.…”
Section: Effects Of the H/he And Alloying Elements On The Healing Promentioning
confidence: 96%
“…First principles calculations by Suzudo et al [49] suggested that the stable configuration of alloying elements Re and Os solutes in W was a mixed dumbbell with a W atom that migrates three-dimensionally. The intrinsic SIA in W is a crowdion migrating one-dimensionally.…”
Section: Effects Of the H/he And Alloying Elements On The Healing Promentioning
confidence: 99%
“…The W-Re binary system is less extensively studied than Fe-Cr, however, recent studies have used a similar on-lattice approach, with a DFT parameterised pairwise energy model, and solute concentration dependant interactions [19]. In W-Re, the mixed interstitial dumbbell is thought to be of particular importance, as unlike the selfinterstitial which is confined to 1D motion, the mixed interstitial is able to move through a series of rotations and translations, to effectively migrate in 3D [20][21][22]. This increased mobility of the mixed interstitial has been shown to facilitate the nucleation and growth of Re clusters in KMC models, despite the predicted solid solution.…”
Section: Introductionmentioning
confidence: 99%